THE HEMATOLOGICAL SIDE EFFECTS ASSOCIATED WITH COMBINATION ANTIVIRAL THERAPY (CONVENTIONAL INTERFERON AND RIBAVARIN) IN PATIENTS WITH HEPATITIS “C” INFECTION - Khalid Amin; Dilshad Muhammad; Masood Javed (Journal of University Medical & Dental College, 2015)
ABSTRACT INTRODUCTION: Hepatitis C virus infection is a major cause of chronic hepatic diseases. According to WHO statistics, the global prevalence of HCV is 3.1%. In East Mediterranean Region (including Pakistan), the prevalence is 4.6%. The most effective therapeutic regimen for infection with hepatitis C virus (HCV) is the combination of interferon alfa and ribavirin (combination therapy) and is effective in approximately 80% of patients infected with hepatitis C virus. The side effects of combination therapy predominantly include hematological abnormalities along with fatigue, inﬂuenza-like symptoms, gastrointestinal disturbances and neuropsychiatric symptoms. OBJECTIVE: To evaluate the frequency of Haematological side effects with combination antiviral therapy (interferon and ribavarin) in patients with hepatitis ’C’ Infection. STUDY DESIGN: Descriptive case series SETTING: Department of Medicine, DHQ Hospital, Faisalabad STUDY DURATION: th th Six months from 29 November 2013 to 29 May 2014 MATERIALS AND METHODS: Total 150 patients with the diagnosis of Hepatitis C were included. Hemoglobin, Leukocyte count and Platelet count was sent before after 2 weeks and then after every four weeks of starting antiviral therapy in DHQ, hospital Laboratory. Informed consent was taken .The primary outcome measure was the frequency of hematological side effects associated with Interferon and Ribavirin in these patients. RESULTS: A total of 150 patients in Medicine Department DHQ were included in the study. Out of these 150 patients, 66(44%) were male and 84(56%) were female. Mean age of the patients was 36.58+ 3.975 (range 20-45 years). Mean hemoglobin level before starting Antiviral therapy was 13.0g/dl (range 11.0-16.0g/dl). Clinically signiﬁcant anemia (Hb< 9g/dl) occurred in 73% of the patients after starting the therapy. The mean drop in the hemoglobin concentration in the ﬁrst two 9weeks of the treatment was 3 g/dl. Leucopenia (<3 x10 /L) occurred in 56 % of the patients and all 9patients recovered after antiviral therapy. Thrombocytopenia (<150 X 10 /L) occurred in 63% of the patients which was insigniﬁcant clinically because platelet counts as low as 50 x 109/L was very well tolerated. Out of total 56 males, anemia was present in 47(71%), leucopenia in 38 (57%) and thrombocytopenia in 41 (62%). Out of 84 females, anemia was present in 63(75%), leucopenia in 46 (55%) and thrombocytopenia in 54 (64%). CONCLUSION: Antiviral therapy is associated with hematological side effects. However, the side effects should be monitored regularly during the therapy to avoid complications and dose of the therapy should be adjusted.